“Forbidden” Disulfides: Their Role as Redox Switches - Wouters, M. A.; George, R. A.; Haworth, N. L. (Current Protein and Peptide Science, 2007)
Seminal studies by Richardson [1] and Thornton [2] defined the constraints imposed by protein structure on disulfide formation and flagged forbidden regions of primary or secondary structure seemingly incapable of forming disulfide bonds between resident cysteine pairs. With respect to secondary structure, disulfide bonds were not found between cysteine pairs: A. on adjacent β-stands [1]; B. in a single helix or strand [2]; C. on non-adjacent strands of the same β-sheet [2]. In primary structure, disulfide bonds were not found between cysteine pairs: D. adjacent in the sequence [2]. In the intervening years it has become apparent that all these forbidden regions are indeed occupied by disulfide-bonded cysteines, albeit rather strained ones. It has been observed that sources of strain in a protein structure, such as residues in forbidden regions of the Ramachandran plot and cis-peptide bonds, are found in functionally important regions of the protein and warrant further investigation [3-5]. Like the Ramachandran plot, the earlier studies by Richardson [1] and Thornton [2] have identified a fundamental truth in protein stereochemistry: “forbidden” disulfides adopt strained conformations, but there is likely a functional reason for this. Emerging evidence supports a role for forbidden disulfides in redoxregulation of proteins.
Keywords: major histocompatibility complex